2022
DOI: 10.1097/01.numa.0000821708.46746.6f
|View full text |Cite
|
Sign up to set email alerts
|

Quality improvement engagement

Abstract: Historically, frontline nurses in collaboration with nursing leadership have engaged in quality improvement (QI) initiatives to transform healthcare. Recently, however, reports indicate that engagement in QI is low among frontline nurses. Using a national sample, researchers identified barriers to and facilitators of engagement in QI by nursing role that may inform future engagement strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
(51 reference statements)
0
2
0
Order By: Relevance
“…Research has shown that the provision of a clear protocol improves adherence 8 . Identification of barriers and facilitators in a quality improvement project is essential for staff engagement 20 . The GRiP analysis revealed the barriers nurses faced in the implementation of this project.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has shown that the provision of a clear protocol improves adherence 8 . Identification of barriers and facilitators in a quality improvement project is essential for staff engagement 20 . The GRiP analysis revealed the barriers nurses faced in the implementation of this project.…”
Section: Discussionmentioning
confidence: 99%
“…8 Identification of barriers and facilitators in a quality improvement project is essential for staff engagement. 20 The GRiP analysis revealed the barriers nurses faced in the implementation of this project. Modifications were made to increase accessibility of resources.…”
Section: Discussionmentioning
confidence: 99%